Estudio de la osteología radiográfica de la rana pipa (Pipa pipa) - Grandez R., Ricardo (2018)
For the study of the radiographic osteology of the Pipa pipe frog, six adult specimens apparently in good health and kept in captivity were used. The MinXray® HF 100 X-ray equipment was used to obtain the radiographic images, analyze the radiographic characteristics and determine the size (length and width) of the head, post-cranial skeleton, shoulder girdle, anterior and posterior limbs. These frogs present the pre-sacral vertebrae I and II fused, and the sacrum fused to the thin urostil. Pipa pipe scapular waist is pseudo-firmisternal. It was possible to identify the bones that make up this region, including the coracoides. The relation between the measures of the tibial-fibula length added to the length of the foot with the corporal length corresponded to 85%.